Evaluation of 20 corn hybrids for silage agronomic characteristics - R.N. Sonon; B.S. Dalke; R. Suazo; L. Pfaff; K.K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1992)
Twenty corn hybrids were grown under irrigation and harvested at 90 % of the kernel milk line. Hybrid had a significant effect on plant height, whole-plant dry matter (DM) and DM yield, grain yield, stover yield, and plant part proportions. The highest whole-plant DM (45.9%) was for Cargill 7997, whereas the lowest was for Cargill 4327 (30.1%). Cargill 8427 and Pioneer 3245 had the highest wholeplant DM and grain yields, whereas Cargill 4327 was lowest. Grain yield and the percentage of grain in the whole-plant DM increased as the plant height increased.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Corn; Hybrid; Silage; Yield